Holocaust monuments and memorials in Central Europe - Janáčová, Eva (De Gruyter series in Holocaust studies and antisemitism, 2025)
Holocaust monuments in Central Europe, especially in today’s Czech Republic, Poland, Hungary, and Germany, have received surprisingly little academic attention. Yet these sites of memory offer deep insight into the individual, collective and cultural memory of the tragedy of the Holocaust.